Autism spectrum disorder in a rural community in Bangladesh: A mid‐childhood assessment. Issue 2 (7th December 2021) - Ali, Hasmot; Rahman, Hafizur; Lee, Li‐Ching; Khan, Naila Z.; Wu, Lee Shu‐Fune; Mehra, Sucheta; Mitra, Maithilee; Labrique, Alain B.; West, Keith P.; Christian, Parul
Abstract: Population‐based studies employing standardized diagnostics are needed to determine the burden of autism spectrum disorder (ASD) in low‐resource settings. A community‐based study was conducted among 8–11 year old children in rural, northwestern Bangladesh to establish the prevalence of ASD. A standardized screening and diagnosis protocol was adapted and deployed comprising the social communication questionnaire (SCQ), and the autism diagnostic observation schedule 2, (ADOS‐2), and the autism diagnostic interview, revised (ADI‐R), respectively. A year‐long research training was conducted for a clinical psychologist to be certified to administer ADOS‐2 and ADI‐R. Over 8000 children were visited at home and administered the SCQ leading to some, based on their score, being further evaluated using the ADOS‐2 and ADI‐R by the clinical psychologist. Based on ADOS‐2 applying the diagnoses of autism or autism spectrum, the prevalence was 40 (95% CI: 27, 54) per 10, 000. Autistic disorder using ADI‐R was found at 12 (95% CI: 5, 20) per 10, 000. Boys were at a higher risk than girls with the rates among boys being 46 (95% CI: 25, 67) using ADOS‐2 and 19 (95% CI:6, 33) using ADI‐R. Among girls the rates were 34 (95% CI:16, 52) and 5 (95% CI:0, 12) per 10, 000, respectively. Challenges to undertaking ASD research in a rural South Asian context are discussed. There was a low‐to‐moderate prevalence of ASD in a rural, child population in Bangladesh. Future research is needed to estimate rates of ASD and its causes and socioeconomic consequences in rural and urban settings of South Asia. Lay Summary: In a study of over 8000, 8–11 year old children in a rural area of Bangladesh, two to four out of 1000 had ASD. Boys more than girls had ASD. Conducting ASD assessment in this setting was difficult, but more such research is needed to understand what causes ASD and its consequences for the individual, families and the society in rural and urban areas of low‐income countries.